How to design and teach a blended course for hard-to-reach adult learners - Lencastre, José Alberto (2021)
In recent years, with easy access to ever-faster and integrated Internet technologies, blended courses have been a safe wager for adult education. Blended courses combine the best of faceto-face classes, such as affective relationships, with all the advantages of online environments, such as interactivity and the flexibility of learning anytime or anywhere. These transformations also allow the use of pedagogical strategies that promote students' development respecting their different ways and rhythms of learning according to their competences and personal interests. Regardless, it is challenging to design and teach a blended course that might be a meaningful learning experience for hard-to-reach adult learners. It requires specific knowledge to each situation and environment. Blended courses are not only those in which face-to-face classes are complemented by online learning but also uses a pedagogy that settles the primary responsibility for learning on the student. They are student-centred courses. The role of the course designer is to create opportunities that promote personalised and collaborative learning. Starting with data from a questionnaire applied to women refugees regarding their educational needs, this article explains how to develop or adapt the curriculum, design learning sequences, manage the online session and facilitate the learners' learning experience. This study’s primary focus was writing an accessible manuscript to all teachers and trainers.